Increase in the Th1-Cell-Based Immune Response in Healthy Workers Exposed to Low-Dose Radiation - Immune System Status of Radiology Staff - Gholamreza Karimi; Mahdi Balali-Mood; Seyed-Ali Alamdaran; Hassan Badie-Bostan; Elaheh Mohammadi; Adel Ghorani-Azam; Mahmood Sadeghi; Bamdad Riahi-Zanjani (Korean Pharmacopuncture Institute, 2017)
Objectives: Radiation is one of the most important sources of free radical (such as reactive oxygen species) production, which plays an essential role in the etiology of over hundred diseases. The aim of the study was to investigate some immune parameters and hematological indices in healthy workers of the Radiology Department, University Hospital of Mashhad, Iran. Methods: The study was performed on 50 healthy workers: 30 radiology staff as the case group and 20 laboratory workers as the control group. The radiation dose received by the radiology staff participating in the study was less than the annual maximum permissible level, 50 millisievert. Hematological parameters, lymphocyte proliferation and cytokine production were studied in both groups. Results: Among healthy radiology workers, the hematological indices did not differ statistically; however, their proliferation indices and IFN-γ levels showed significant increases in parallel with decreases in the IL-4 levels as compared